Cognitive Deficits in Patients of Depressive Disorder - Jat, Muhammad Ilyas; Rajper, Ali Bux; Kataria, Chooni Lal (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To determine the frequency of cognitive deficits in patients of Depressive disorder. METHODOLOGY: This cross-sectional study was conducted at Jinnah Post Graduate Medical Centre (JPMC), Karachi,from September 2018 to March 2019. The sample size of 250 was calculated through customary techniques, and the sampling technique was non-probability consecutive sampling. Those patients who were diagnosed with cases of depressive disorder were enrolled in the study. The data were analyzed using SPSS (Statistical Packages of Social Sciences) version 22.0. RESULTS: Out of the total of 250 cases, 114 (45.60%) were males, and 136 (54.40%) were females with an average age of 33.62±11.07 years. Among 250, the majority, 178 (71.20%), were married and Illiterate 90 (36.00%). Among all participants, 136 (54.4%) belonged to middle socio-economic and 120 (68.0%) were household by occupation. Out of 250 cases, 135 (54%) were drug naïve, while 114 (45.6%) were on active treatment. Cognitive dysfunction was present among 169 (67.6%). Educational status, treatment status, and duration of diseases were considerably related, with cognitive dysfunction having a p-value of less than 0.05. CONCLUSION: The rate of Cognitive dysfunctions among patients with depressive disorder is high and alarming. KEY WORDS: Cognitive deficits, Depressive disorder, Frequency, Patients, Perceived Dysfunction Questionnaire, Score.